Step
*
1
2
of Lemma
bag-summation-equal-implies-all-equal
1. T : Type
2. b : bag(T)
3. f : {x:T| x ↓∈ b}  ⟶ ℤ
4. g : {x:T| x ↓∈ b}  ⟶ ℤ
5. (∀x:{x:T| x ↓∈ b} . (x ↓∈ b 
⇒ (f[x] = g[x] ∈ ℤ))) supposing 
      ((Σ(x∈b). g[x] ≤ Σ(x∈b). f[x]) and 
      (∀x:{x:T| x ↓∈ b} . (x ↓∈ b 
⇒ (f[x] ≤ g[x]))))
6. ∀x:T. (x ↓∈ b 
⇒ (f[x] ≤ g[x]))
⊢ istype(Σ(x∈b). g[x] ≤ Σ(x∈b). f[x])
BY
{ ((Assert Σ(x∈b). g[x] ≤ Σ(x∈b). f[x] ∈ Type BY
          ((Assert b ∈ bag({x:T| x ↓∈ b} ) BY (BLemma `bag-subtype` THEN Auto)) THEN Auto THEN D 0 THEN Reduce 0 THEN Au\000Cto))
   THEN Auto
   ) }
Latex:
Latex:
1.  T  :  Type
2.  b  :  bag(T)
3.  f  :  \{x:T|  x  \mdownarrow{}\mmember{}  b\}    {}\mrightarrow{}  \mBbbZ{}
4.  g  :  \{x:T|  x  \mdownarrow{}\mmember{}  b\}    {}\mrightarrow{}  \mBbbZ{}
5.  (\mforall{}x:\{x:T|  x  \mdownarrow{}\mmember{}  b\}  .  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  =  g[x])))  supposing 
            ((\mSigma{}(x\mmember{}b).  g[x]  \mleq{}  \mSigma{}(x\mmember{}b).  f[x])  and 
            (\mforall{}x:\{x:T|  x  \mdownarrow{}\mmember{}  b\}  .  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  \mleq{}  g[x]))))
6.  \mforall{}x:T.  (x  \mdownarrow{}\mmember{}  b  {}\mRightarrow{}  (f[x]  \mleq{}  g[x]))
\mvdash{}  istype(\mSigma{}(x\mmember{}b).  g[x]  \mleq{}  \mSigma{}(x\mmember{}b).  f[x])
By
Latex:
((Assert  \mSigma{}(x\mmember{}b).  g[x]  \mleq{}  \mSigma{}(x\mmember{}b).  f[x]  \mmember{}  Type  BY
                ((Assert  b  \mmember{}  bag(\{x:T|  x  \mdownarrow{}\mmember{}  b\}  )  BY
                                (BLemma  `bag-subtype`  THEN  Auto))
                  THEN  Auto
                  THEN  D  0
                  THEN  Reduce  0
                  THEN  Auto))
  THEN  Auto
  )
Home
Index